Self-harm, anxiety, and depression in adolescents attending a public school in a city in southern Minas Gerais, Brazil (Research, Society and Development, 2022)
Objective: The objective of this study was to identify the presence of self-harm behavior among adolescents, the methods and reasons for this behavior, and to assess the association with the sociodemographic, anxiety, and depression variables. Methodology: This is a quantitative, descriptive, cross-sectional study carried out with 73 adolescents attending a school in a city in southern Minas Gerais, Brazil. The data collection instruments used were the following: Characterization, Economic Classification, Functional Assessment of Self - Mutilation, Screen for Child Anxiety Related Emotional Disorders, and the Children's Depression Inventory. Results: Self-harm was evidenced in 84.9% of the participants, 72.6% presented anxiety symptoms, 50.6% presented depression symptoms, and 37.1 % presented suicidal ideation. The methods used for self-harm were the following: poking wounds, hitting and biting oneself, and skin cutting.  The main motivations were the following: to relieve feelings of emptiness or indifference, to cease negative feelings or sensations, and to feel relaxed. Self-harm is associated with the female gender, suicidal ideation, anxiety, and depression. Conclusion: It is concluded that self-harm is a risk factor for suicide and generates significant suffering interfering negatively in the lives of adolescents. The need for greater attention to the mental health of adolescents in the school context is highlighted.